West Syndrome: Response to Valproate - Chandra, Surabhi; Bhave, Anupama; Bhargava, Roli; kumar, Chandrakanta; Kumar, Rashmi (Frontiers in Neurology, 2012)
Management of West syndrome is unsatisfactory. In our clinic we observed that a significant proportion of patients respond to usual dose of valproate. Objective: To prospectively assess the efficacy of valproate in controlling infantile spasms in West syndrome Methods: Consecutive patients presenting with West syndrome to the Pediatric Neurology Clinic or general OPD were enrolled for study. Those who were not on any treatment were given valproate in a dose of 30 mg/kg/day while awaiting investigations. Patients were followed up every 2 weeks. Predefined criteria for definition of West syndrome and response were used. Those showing partial/poor response or relapse on valproate were given hormonal therapy. Results: One hundred children with West syndrome were enrolled. Ninety one children were started on valproate. Of these 36 (39.5%) showed a good response, but 7 later relapsed while on same dose of valproate and 3 were lost to follow up. Later age at onset and typical hypsarrythmia on EEG were associated with good sustained response to valproate while a history of delayed cry at birth was associated with partial or poor response. Sixty two patients who responded poorly to or relapsed on valproate were put on hormonal treatment in addition. Of these 36 (58.1%) had a good response but 11 later relapsed after stopping treatment and 2 were lost to follow up. Conclusions: Valproate may have a role in treatment of West syndrome in a selected group of patients.